2022
DOI: 10.1099/acmi.0.000350
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of Plasmodium falciparum msp-1, msp-2 and glurp vaccine candidate genes in pre-artemisinin era clinical isolates from Lakhimpur district in Assam, Northeast India

Abstract: Background. Northeast India shares its international border with Southeast Asia and has a number of malaria endemic zones. Monitoring genetic diversity of malaria parasites is important in this area as drug resistance and increasing genetic diversity form a vicious cycle in which one favours the development of the other. This retrospective study was done to evaluate the genetic diversity patterns in Plasmodium falciparum strains circulating in North Lakhimpur area of Assam in the pre-artemisinin era and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Allele sizes were determined with two molecular weight standards (100 bp DNA Ladder, New England Biolabs). Alleles were considered identical if the fragment sizes were within the range of 10 bp [ 15 ] and 20 bp [ 6 ] for msp-1 and msp-2 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Allele sizes were determined with two molecular weight standards (100 bp DNA Ladder, New England Biolabs). Alleles were considered identical if the fragment sizes were within the range of 10 bp [ 15 ] and 20 bp [ 6 ] for msp-1 and msp-2 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of MSPs and invasion complex proteins are responsible for erythrocyte invasion. It has been reported that msp1 and msp2 show high levels of genetic polymorphism which may complicate the malaria vaccine development ( 131 ). However, another study reported that MSP1 contains conserved B-cell epitopes indicating that MSP1 could serve as a promising vaccine candidate against P. vivax malaria ( 132 ).…”
Section: Vaccine Candidates Against Plasmodiummentioning
confidence: 99%